Rapid Generation of Leukemogenic Chromosomal Translocations in Vivo Using CRISPR/Cas9. Issue 5 (30th October 2020) - Huang, Yun; Marovca, Blerim; Dettwiler, Susanne; Bode, Peter Karl; Bornhauser, Beat; Bourquin, Jean-Pierre
Abstract : Supplemental Digital Content is available in the text